DINAMIKA POPULASI UDANG CENDANA (Metapenaeus brevicornis) YANG TERTANGKAP PADA SIANG HARI DI PERAIRAN SAMBOJA KUALA KABUPATEN KUTAI KARTANEGARA - Laroibafih, Muhammad Jazuli; Abdunnur; Ramang, Muhammad Syahrir (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
Samboja Kuala is one of the Kelurahan in Samboja District which is an area where most of the population works as fishermen. There are two types of fishery activities in the Samboja Kuala area, namely capture fisheries (fishermen) and aquaculture fisheries. Samboja kuala is a fishery production contributor area for Samboja District, with the dominant catch being shrimp. Yellow shrimp (Metapenaeus brevicornis) is one of the catches of fishermen shrimp in Samboja Kuala Waters. This study aims to determine several parameters of population dynamics using the carapace length data frequency method. The research was conducted in Samboja Kuala waters, Kutai Kartanegara Regency, in November-December 2022. Based on the results of the study, the sex ratio between males and females was 0,05:16,8. The length range in male and female sex is 58,44 mm – 118,5 mm and 37,5 mm – 125,8 mm. And the natural mortality (M) of males and females was 0.958 per year and 1.277 per year, the capture mortality (F) of males and females was -46.94 per year and 0,55 per yearthe capture mortality (F) of males and females was – 0.94 per year and 1.55 per year, the total mortality of males and females was 0.958 per year and 1.277 per year, and the exploitation rates of males and females were 0.33 and 0.50. New additions of males occurred in November by 20,97%. and new additions of females occurred in September by 18,67%.